2022
DOI: 10.1007/s10811-022-02880-2
|View full text |Cite
|
Sign up to set email alerts
|

Edible algae allergenicity – a short report

Abstract: The use of seaweed and algal derived products in the food industry has grown rapidly in recent times. Major areas of expansion have been in Western countries where algae derived commodities are being utilised as edible foods or sources of high value ingredients. However, studies focused on potential allergenicity attributed to these food items, prevalence of allergenicity, and public health awareness are limited. Therefore, the current research summarises the existing literature focused on algal induced allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 86 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first review focused on the topic of allergy to spirulina. There was a short report on edible algal allergenicity published in 2023 [42]; however, in that study, the authors found only two cases of allergy to spirulina since their main aim was to assess general algal allergenicity.…”
Section: Spirulina As An Allergy-inducing Factormentioning
confidence: 99%
“…To the best of our knowledge, this is the first review focused on the topic of allergy to spirulina. There was a short report on edible algal allergenicity published in 2023 [42]; however, in that study, the authors found only two cases of allergy to spirulina since their main aim was to assess general algal allergenicity.…”
Section: Spirulina As An Allergy-inducing Factormentioning
confidence: 99%
“…Currently, a significant need for studies focusing on the allergenic properties of algal proteins is highlighted. Due to the popularization of algae and the expansion of the market for products with their addition, further research in this area and the issuance of an appropriate regulation are necessary (James et al., 2023).…”
Section: Future Development and Challengesmentioning
confidence: 99%
“…Additionally, there is an abundance of cross‐reactive proteins in the sources of novel synthetic foods (e.g., seeds, legumes, and tree nuts), thus increasing the potential of food allergy (Cox et al., 2021). Additionally, Spirulina and Chlorella , key components in microalgae‐based foods, have been related to severe allergic reactions (James et al., 2023; Petrus et al., 2010).…”
Section: Potential Risk Factors In Novel Synthetic Foodsmentioning
confidence: 99%